S1P Lyase siRNA Dampens Malignancy of DLD‐1 Colorectal Cancer Cells. Issue 2 (24th September 2020) - Faqar‐Uz‐Zaman, Wajiha Farha; Schmidt, Katrin G.; Thomas, Dominique; Pfeilschifter, Josef M.; Radeke, Heinfried H.; Schwiebs, Anja
Abstract: Sphingosine‐1‐phosphate lyase 1 (S1P lyase or SGPL1) is an essential sphingosine‐1‐phosphate‐degrading enzyme. Its manipulation favors onset and progression of colorectal cancer and others in vivo . Thus, SGPL1 is an important modulator of cancer initiation. However, in established cancer, the impact of retrospective SGPL1 modulation is elusive. Herein, we analyzed how SGPL1 siRNA affects malignancy of the human colorectal cancer cells DLD‐1 and found that in parallel to the reduction of SGPL1 expression levels, migration, invasion, and differentiation status changed. Diminished SGPL1 expression was accompanied with reduced cell migration and cell invasion in scratch assays and transwell assays, whereas metabolic activity and proliferation was not altered. Decreased migration was attended by increased cell–cell‐adhesion through upregulation of E‐cadherin and formation of cadherin‐actin complexes. Spreading cell islets showed lower vimentin abundance in border cells. Furthermore, SGPL1 siRNA treatment induced expression of epithelial cell differentiation markers, such as intestinal alkaline phosphatase and cytokeratin 20. Hence, interference with SGPL1 expression augmented a partial redifferentiation of colorectal cancer cells toward normal colon epithelial cells. Our investigation showed that SGPL1 siRNA influenced tumorigenic activity of established colorectal cancer cells. We therefore suggest SGPL1 as a target for lowering malignant potential of already existing cancer.